Role of MSK1 in the Malignant Phenotype of Ras-transformed Mouse Fibroblasts - Pérez-Cadahía, Beatriz (American Society for Biochemistry and Molecular Biology, 2011)
Activated by the RAS-MAPK signaling pathway, MSK1 is recruited to immediate-early gene (IEG) regulatory regions, where it phosphorylates histone H3 at Ser-10 or Ser-28. Chromatin remodelers and modifiers are then recruited by 14-3-3 proteins, readers of phosphoserine marks, leading to the occupancy of IEG promoters by the initiation-engaged form of RNA polymerase II and the onset of transcription. In this study, we show that this mechanism of IEG induction, initially elucidated in parental 10T1/2 murine fibroblast cells, applies to metastatic Hras1-transformed Ciras-3 cells. As the RAS-MAPK pathway is constitutively activated in Ciras-3 cells, MSK1 activity and phosphorylated H3 steady-state levels are elevated. We found that steady-state levels of the IEG products AP-1 and COX-2 were also elevated in Ciras-3 cells. When MSK1 activity was inhibited or MSK1 expression was knocked down in Ciras-3 cells, the induction of IEG expression and the steady-state levels of COX-2, FRA-1, and JUN were greatly reduced. Furthermore, MSK1 knockdown Ciras-3 cells lost their malignant phenotype, as reflected by the absence of anchorage-independent growth.